Pembebanan Kerugian Negara terhadap Bendahara oleh Badan Pemeriksa Keuangan - Nurul Islamy Panjaitan (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
The imposition of state losses on the treasurer by the Financial Audit Agency (BPK) is an effort by the state to obtain rights and obligations that should be implemented on the basis of public financial management. The problem of negligence and unlawful acts of authorized officials (treasurers) results in the state experiencing losses, so to overcome this, a process of assessing losses must be implemented. This research uses normative legal research methods to analyze statutory regulations relating to the imposition of state losses by the treasurer. The research results show that the legal provisions governing the imposition of state losses on the treasurer involve a series of processes, including audits by the BPK to assess errors or omissions that caused losses. In this event, the treasurer may be subject to sanctions and legal responsibility due to negligence and unlawful acts at the level of the violation that occurred. Apart from that, the BPK also has an important role in providing recommendations for improvement and prevention so that similar incidents do not happen again in the future. That the system of charging state losses to the treasurer needs to continue to be updated and perfected to make it more effective and efficient in maintaining the integrity of public finances. Apart from that, there is a need for the BPK to play an active role in providing constructive suggestions and recommendations to prevent financial violations that could harm the state.